SUPPLY CHAIN ANALYSIS OF PRAWN (PENAEUS MONODON FABRICIUS) IN NORTHERN MINDANAO, PHILIPPINES - Guigue, Gemma M (Journal of Agriculture and Technology Management; Vol 24 No 1 (2021): Vol 24 No 1 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 January - June 2021 Issue, 2021)
The study investigated the prawn growers and traders in the Northern Mindanao Region 10, Philippines for better government support and to enable sustainability in the supply chain of the prawn industry. Focus group discussion was conducted and survey instrument was used to document and interview players in the supply chain. Major players were in Tangub City and Municipality of Bonifacio, Ozamis City, and Lanao del Norte. The latter was identified as the most profitable supply chain in Northern Mindanao. Prawn traders were rated high in flexibility, responsiveness and concern on product and process quality compared to prawn growers. Traders reap greater profitability. However, both growers and traders shared similar critical logistic issues on environmental concerns. Certain inefficiencies are also identified in the study, such as asymmetric market information, poor farm to market road, lack or absence of market weight standards, high transaction cost, and determination of the selling price is generally based on average body weight which may not be accurate and may prove disadvantageous to prawn growers. In the significance of the findings of the study, the following recommendations are formulated. Producers shall be empowered to push for standardized price determination. Strengthened government programs through agri-fishery infrastructures and technical assistance on water pollution management.